Using Podcast to Teach Listening Comprehension - Pratiwi, Agil; Hidayati, Istiqlaliah Nurul; Gusnadi, Gusnadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
Listening is important to be learned by students in learning English language. However, students find it hard to comprehend and understand the language, because students are not accustom to the language. To help students to accustom to the language and improve listening skill needs proper medium in learning activity. Using podcast as medium in learning listening is expected to help the students accustom to the language. The research was conducted at SMK Putra Pakuan that involved 33 students of X TKJ as the sample from the total population 135 students of tenth grade. Pre-experimental method and one group pre-test post-test design were used. T-test formula is used to analyze the data. Based on data calculation, the result of t-test value is 4.26. Meanwhile, t-table value is 2.03 at significant level 0.05 with the degree of freedom (df) is 32. It shows that the t-test value is higher than t-table value (4.262.03). It means the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that podcast has an effect on students listening comprehension.